Maksim Relevansi pada Film “Calon Lurah” Karya Hajar Pamuji (Tinjauan Pragmatis) - Windha Pradhita Citra Yuli Hapsari; Surana Surana (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to analyze the application of the maxim of relevance in the film